The prospects of adaptive selection of early onion sorts - Борисенко, Л. Д.; Катаєва, Т. Є. (Scientific Progress & Innovations, 2012)
The results of many years investigations of selected onion material in two geographic locations are introduced in this article. After environmental tests were done a number of promising early-maturing lines of short (up to 100 days) vegetative period onions, as well as high-yield samples, cellarage suited and biotic and abiotic factors resistant were assorted. The efficiency of selections on morphological features which should be expedited productivity choice was proved . The plants from the sources that had the greatest adaptive potential due to agronomic traits complex were chosen for the further working.